2019
DOI: 10.7150/jca.31598
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of pretreatment red blood cell distribution width in patients with cancer: A meta-analysis of 49 studies

Abstract: Red blood cell distribution width (RDW) has been recently demonstrated to be a predictor of inflammation. High pretreatment RDW level is associated with poor survival outcomes in various malignancies, although the results are controversial. We aimed to investigate the prognostic role of RDW. A systematic literature search was performed in MEDLINE and EMBASE till April 2018. Pooled hazard ratios (HRs) were estimated for overall survival (OS) and combined disease-free survival, progression-free survival, and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 96 publications
(103 reference statements)
5
63
0
1
Order By: Relevance
“…This phenomenon will eventually lead to variations in the sizes of the red blood cells involved in the circulatory response in the peripheral blood, as manifested by increased RDW levels [25]. Moreover, the increase in RDW may be related to oxidative stress response in the body [26]. Red blood cells, the most important oxygen-carrying medium in the body, will induce hypoxia or a hypoxic microenvironment when they differ in size or their functions are impaired.…”
Section: Plos Onementioning
confidence: 99%
“…This phenomenon will eventually lead to variations in the sizes of the red blood cells involved in the circulatory response in the peripheral blood, as manifested by increased RDW levels [25]. Moreover, the increase in RDW may be related to oxidative stress response in the body [26]. Red blood cells, the most important oxygen-carrying medium in the body, will induce hypoxia or a hypoxic microenvironment when they differ in size or their functions are impaired.…”
Section: Plos Onementioning
confidence: 99%
“…It is largely accepted that multiple forms of pathologies, both related to abnormal structure RBC membrane or cytosolic proteins and lipids, as well as systemic disorders such as cancer, diabetes, cardiovascular diseases, sepsis and other diseases of inflammation are associated with anemia, RBC damage and their premature removal from the circulation and increase in their heterogeneity (e.g., Salvagno et al, 2015;Feng et al, 2017;Ahmad et al, 2018;Ko et al, 2018;Yin et al, 2018;Parizadeh et al, 2019;Wang et al, 2019). The causes and consequences as well as predictive power of this increase in variability of RBC properties is out of the scope of this review but deserve special attention.…”
Section: Physical Activity High Altitude and Other Stress Conditionsmentioning
confidence: 99%
“…Increase in RDW values have been suggested as a diagnostic and prognostic tool in colon cancer patients (16,17). Very recently, in a meta-analysis of 49 studies, elevated pretreatment RDW level was suggested as a negative predictor for cancer prognosis (18). We determined a significant increase in RDW values after chemotherapy which may be associated with increased inflammatory response.…”
Section: Discussionmentioning
confidence: 96%